2011
DOI: 10.1177/0021998311413684
|View full text |Cite
|
Sign up to set email alerts
|

Effective elastic properties and stress distribution of 2D biaxial nonorthogonally braided composites

Abstract: Due to the interlacement of tows, the architecture of braided composites is complex, especially for the nonorthogonal braid in which the tow has various cross sections along the towpath. The microscopic mechanical analysis is highly sensitive to the geometric architecture, which causes great difficulties for the research on material behavior of nonorthogonal braid. In this article, a finite element model has been proposed to investigate the effective elastic properties and stress distribution of 2D biaxial non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…In this model, cross‐sections of the fiber yarns were fitted as ellipses, and their geometric parameters were recorded. Because of the regular array of tows in the textile composite, an RVE model, which is the minimum periodic structure, is singled out and studied instead of the whole structure . According to the definition of the RVE and the structure, which is shown in Figure in ref., we chose the smallest periodic unit as the RVE size.…”
Section: Finite Element Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In this model, cross‐sections of the fiber yarns were fitted as ellipses, and their geometric parameters were recorded. Because of the regular array of tows in the textile composite, an RVE model, which is the minimum periodic structure, is singled out and studied instead of the whole structure . According to the definition of the RVE and the structure, which is shown in Figure in ref., we chose the smallest periodic unit as the RVE size.…”
Section: Finite Element Modelmentioning
confidence: 99%
“…Because of the regular array of tows in the textile composite, an RVE model, which is the minimum periodic structure, is singled out and studied instead of the whole structure . According to the definition of the RVE and the structure, which is shown in Figure in ref., we chose the smallest periodic unit as the RVE size. For the yarns, the major and minor axes of the cross‐sectional ellipse were 0.42 and 0.14 mm long, respectively.…”
Section: Finite Element Modelmentioning
confidence: 99%
“…Sun and Sun 16 indicated that braiding angle went down with increased pitch length. The surface braiding angle and pitch length are also important parameter of influencing the mechanical behavior of braided composite, 15,[17][18][19][20] for instance, as the surface braiding angle increase, the mismatch between longitudinal and transverse stiffness become less pronounced, with a tendency toward balanced Poisson's ratios for the [0°/± 60°] material. 21 Zou et al 22 indicated that the radial force is higher with shorter pitch length when surface braiding angle is fixed.…”
Section: Introductionmentioning
confidence: 99%
“…Jiang et al presented a multiphase finite element method based on the helix geometry model to predict the effective elastic constants and strength of 3D braided composites under tension loading. Qu et al proposed a finite element model to investigate the effective elastic properties and stress distribution of 2D biaxial nonorthogonally braided composites.…”
Section: Introductionmentioning
confidence: 99%